Experiment on Rapidly Intensifying Cyclones Over the Atlantic - BATTELLE MEMORIAL INST COLUMBUS OH (1990)
The Experiment on Rapidly Intensifying Cyclones over the Atlantic (ERICA) field study is designed to determine physical mechanisms and processes, and their critical spatial and temporal combinations, which can account for the wintertime phenomenon of explosively-developing over-ocean atmospheric storms. The core field experiment will be supplemented by the substantial participation of many other agencies and universities from the United States and Canada. Data will be obtained over the North Atlantic Ocean from Cape Hatteras to beyond Newfoundland, centered east of Cape Cod and south of Nova Scotia. The general timing and siting is chosen through consideration of historical storm occurrence data. Measurements on individual rapidly-intensifying storms will be made from aircraft, buoys, and satellites, and by soundings and radars. Observations made during the pre-ERICA field test, January 1988, are discussed. This article describes the measurement objectives and the ways by which the field data will be collected.